A Comparison of the Surface Pressure Distribution of Circular Cables and Helical Fillet Cables under Wind Attack: A Wind Tunnel Test Study - Nguyen, Duy Thao; Vo, Duy Hung; Do, Viet Hai (Engineering, Technology & Applied Science Research, 2024)
This study examines the aerodynamic performance and surface pressure distribution features of circular and helical fillet stay cables when subjected to wind using wind tunnel testing. The research seeks to clarify the aerodynamic performance disparities between conventional circular stay cables and helical fillet cables, providing valuable insights into their appropriateness for cable-supported structures exposed to wind-induced vibrations. The study initially investigates the aerodynamic efficiency of circular and helical fillet cables. Afterward, the wind tunnel captures the distribution of surface pressure on both cable surfaces. The findings suggest that circular stay cables may undergo cable dry galloping, whereas helical fillet cables demonstrate stability when subjected to wind forces. Furthermore, there are noticeable differences in the surface pressure distribution patterns between circular stay cables and helical fillet cables. Circular stay cables provide a symmetric distribution of pressure, with uniform pressure magnitudes along their surfaces, forming a symmetric pattern. On the other hand, helical fillet cables exhibit modified airflow patterns, leading to asymmetric pressure on the cable surface. Furthermore, the dry galloping observed in circular cables is attributed to the presence of low-frequency components. In contrast, helical fillet cables exhibit a more regulated incidence of low-frequency vortices, making them less prone to wind-induced vibrations.